Isolation and preliminary evaluation of a low-molecular-mass antigen preparation for improved detection of Helicobacter pylori immunoglobulin G antibodies. - Andersen, L P (1995)
Previously, immunoglobulin G (IgG) antibodies to five antigens with a relative molecular mass of between 15 and 30 kDa from Helicobacter pylori were found to be significantly more frequent in H. pylori-infected patients than in noninfected patients. In this study, these specific low-molecular-mass (LMW) antigens were separated by ultrafiltration of whole-cell sonicates. The LMW antigen preparation was evaluated by enzyme-linked immunosorbent assay with serum samples from 76 children with abdominal symptoms and 151 adults with dyspeptic symptoms. H. pylori was cultured or seen in 40 (53%) children and 83 (55%) adults. Increased antibody levels to H. pylori were found in serum from 35 (46%) children and 88 (58%) adults. Values for sensitivity, specificity, and predictive value of positive and negative results of the test were higher with LMW antigens than with the heat-stable antigen previously described. The low specificity and predictive value of a positive result were due to seropositive results for 21 persons with a negative culture for H. pylori and negative microscopy results for Helicobacter-like organisms in biopsies from gastric mucosa. Histologically, chronic gastritis was demonstrated in 43% of these persons, and 19% had peptic ulcer, indicating that they have or have had H. pylori infection. Specific antibodies to H. pylori were confirmed in all 21 patients by the Western immunoblot technique. Use of the LMW antigen improved the IgG antibody detection in patients with H. pylori infection, even though the results reflect the difficulties in establishing a true gold standard for diagnosis of H. pylori infection.